2018
DOI: 10.20473/jisebi.4.1.18-24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Software Quality to Improve Application Performance Using Mc Call Model

Abstract: The existence of software should have more value to improve the performance of the organization in addition to having the primary function to automate. Before being implemented in an operational environment, software must pass the test gradually to ensure that the software is functioning properly, meeting user needs and providing convenience for users to use it. This test is performed on a web-based application, by taking a test case in an e-SAP application. E-SAP is an application used to monitor teaching and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The better the system looks, the easier the user is to use the system and the easier it is to learn (13) Users can upload and download documents quickly (3) (10). The reliability factor of 77% is considered by the user is good because the input is not in accordance with the format on all modules there is an error notification, all outputs needed in accordance with the user's desired format such as Lesson Plan documents, Syllabus, Schedule and others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The better the system looks, the easier the user is to use the system and the easier it is to learn (13) Users can upload and download documents quickly (3) (10). The reliability factor of 77% is considered by the user is good because the input is not in accordance with the format on all modules there is an error notification, all outputs needed in accordance with the user's desired format such as Lesson Plan documents, Syllabus, Schedule and others.…”
Section: Resultsmentioning
confidence: 99%
“…While the assessment range for the weight of each quality factor and the weight for each metric can be seen in Table 2. After determining the scale of the assessment, the question instrument was made based on McCall's theory (10) (11). Analysis of questionnaire data is done quantitatively using McCall's formula.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that all items were positively evaluated in terms of functionality, usability, and efficiency. Such dimensions directly influence the quality of the web software, so by assessing them, the performance of this new technology can be improved (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an application must be present for a business activity to execute better [3]. Technology was required to enhance their effectiveness, mainly when COVID surfaced [4]. For the business to improve the application's functionality, this evaluation must be carried out to determine how much is required to know the quality of the software [5].…”
Section: Introductionmentioning
confidence: 99%